Tanmiyah Waqf al-Manāfi min Ajl al-Istiqlāliyah fī Majāli al-Iqtiṣād: Dirāsah fī Ma’had Tazakkā al-‘Aṣrī - Mulyono Jamal; Mohammad Hanief Sirajulhuda; Muhammad Aunurrochim Mas'ad Saleh; Khurun'in Zahro' (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
The excellent potential of benefit waqf has not been fully realized since nāẓir or the community failed to develop a strategy and did not innovate enough on the advantages of waqf and its administration. One of the successful principals in administering benefits waqf is the Tazakka Modern Boarding School with its innovation and programs on endowment benefits. This study intends to identify the benefit waqf development approach for Tazakka Modern Boarding School for economic independence. With a descriptive strategy, this study employs a qualitative methodology. The results of this study demonstrate that the development of benefit waqf in Tazakka is advantageous for economic independence with three distinct benefit waqf categories. So, for future researchers to be able to discuss professional nāẓir with good management and strategy, to maximize the potential and role of beneficial waqf in improving the economy and people's welfare.